Infected Endocarditis in Intravenous Drug Abusers - Agnita Irawaty; Ardian J. Saputra (Cermin Dunia Kedokteran, 2017)
Infective endocarditis (IE) is one of the most severe complications in intravenous drug abusers (IVDA). IE usually involves the tricuspid valve (70%). Commonly, these patients develop endocarditis on the right side heart valves. Staphylococcus aureus is the most common etiologic agent, and has a relatively good prognosis. We describe a case of Tricuspid Valve Endocarditis (TVE) in a 33-year-old male with a history of intravenous drug users.Drug abuse and addiction are major burdens to society. Overdose, cutaneous complications, pulmonary embolism, infective endocarditis (IE), community-acquired pneumonia, pulmonary tuberculosis, septicemia, and transmission of blood-borne infections are well-known complications of IVDA. Tricuspid Valve Endocarditis (TVE) occurs predominantly in IVDA and Staphylococcus aureus is the usualetiology (60%-70%).